(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article considers the issue of the obsolete nouns in the language of the monuments of the Middle Ages in comparison with the modern Kazakh language. A lot of nouns in the Kazakh language have changed their external form but preserved the internal lexical meaning. On the contrary, another group of nouns preserved the form changing their internal lexical meaning. Some of them have lost their old meaning, while others acquired new lexical meanings. All this may explain the «obsolescence» of nouns. It can also serve as an explanation for the other parts of speech.